2004
DOI: 10.1051/rnd:2004017
|View full text |Cite
|
Sign up to set email alerts
|

Development of swamp buffalo (Bubalus bubalis) embryos after parthenogenetic activation and nuclear transfer using serum fed or starved fetal fibroblasts

Abstract: -The knowledge of oocyte activation and somatic cell nuclear transfer in the swamp buffalo (Bubalus bubalis) is extremely rare. The objectives of this study were the following: (1) to investigate the various activation treatments on the parthenogenetic development of buffalo oocytes, (2) to examine the events of nuclear remodeling and in the in vitro development of cloned buffalo embryos reconstructed with serum fed or starved fetal fibroblats, and (3) to investigate the in vivo development of cloned embryos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 42 publications
4
17
2
Order By: Relevance
“…The causes of abortion remain unclear, although incomplete genetic reprogramming or abnormal gene expression of nuclear transfer embryos may contribute to high abortion rates after embryo transfer (Saikhun et al, 2004). Incidence of loss between day 90 of gestation and calving was 43.7% for bovine adult somatic clones (Heyman et al, 2002), which was much lower than those encountered in the current study.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The causes of abortion remain unclear, although incomplete genetic reprogramming or abnormal gene expression of nuclear transfer embryos may contribute to high abortion rates after embryo transfer (Saikhun et al, 2004). Incidence of loss between day 90 of gestation and calving was 43.7% for bovine adult somatic clones (Heyman et al, 2002), which was much lower than those encountered in the current study.…”
Section: Discussioncontrasting
confidence: 71%
“…In this study, the 29% pregnancy rate at day 60 was higher than that reported by Saikhun et al (2004), who performed SCNT in synchronized buffaloes. In animals derived from cloning or in vitro culture procedures, a high incidence of placental abnormalities is found during both early and late gestation (Hill et al, 2000).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Embryo production rate was examined under inverted microscope (Nikon Inc., Tokyo, Japan) to record the number of cleaved embryos at 48 h post-activation (h.p.a), percentage of embryos with 8-to 16-cells at 94-96 h.p.a and blastocyst formation at 168-192 h.p.a. Blastocysts were stained with Hoechst 33342 for 1 h and the total number of their nuclei was counted as described earlier by Saikhun et al (2004).…”
Section: Embryo Culturementioning
confidence: 99%
“…Blastocysts were stained with Hoechst 33342 for 1 h and the total number of their nuclei was counted as described earlier by Saikhun et al (2004).…”
Section: Embryo Culturementioning
confidence: 99%